1979
DOI: 10.3109/00365597909179995
|View full text |Cite
|
Sign up to set email alerts
|

Prostatitis in the Rat

Abstract: A high incidence of spontaneous, non-acute, age-dependent prostatitis was observed in the lateral prostate of Copenhagen rats and Wistar rats. The lumen of infected acini was filled with polymorphonuclear leucocytes, shed epithelial cells and cell residues. Epithelial cells lining such acini showed degenerative changes. Lymphocytes and macrophages were seen in the stroma. A histochemically observed increase in acid phosphatase and beta-glucuronidase activity in affected epithelial cells may indicate an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 11 publications
3
16
0
1
Order By: Relevance
“…Models evaluating spontaneous, age-and genetically dependent prostatitis [7,8], and bacterial prostatitis [5] were followed by models demonstrating the autoimmune characteristics of the inflammation [9,10]. The model described in this paper examined the pathogenesis of inflammation from a mucosal surface perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Models evaluating spontaneous, age-and genetically dependent prostatitis [7,8], and bacterial prostatitis [5] were followed by models demonstrating the autoimmune characteristics of the inflammation [9,10]. The model described in this paper examined the pathogenesis of inflammation from a mucosal surface perspective.…”
Section: Discussionmentioning
confidence: 99%
“…65 By the age of 20 weeks, 88% of Copenhagen rats develop spontaneous lateral prostatic lobe inflammation; in contrast, prostatitis develops in only 6% of (Copenhagen  Fischer) 344 males. 66 Naslund et al 67 reported that 12-week-old Lewis, Wistar, and Sprague-Dawley males had a 30, 0 and 0% incidence of spontaneous lateral prostate inflammation, respectively; the incidence of this lobe specific nonbacterial prostate inflammation was increased considerably in older (40-to 52-week-old) Lewis (72%) and Wistar (27%) males, but not in Sprague-Dawley rats (0%).…”
Section: Rat Models Of Prostatitismentioning
confidence: 99%
“…By employing tissuerecombination techniques, it has been demonstrated that the growth and differentiation of normal epithelium is regulated either inductively or permissively by neighboring mesenchymal components (5,6). Studies of stromal-epithelial interaction in the prostate gland revealed that mesenchyme isolated from the fetal urogenital sinus (7,8) but not from the prostate of newborns (9) or adults (10) can stimulate proliferation of well-differentiated adult epithelium. Mesenchymal mediation of sex steroid action on glandular epithelium has also been demonstrated.…”
mentioning
confidence: 99%